Lady Windermere's fan - Wilde, Oscar 1854-1900 (Lost silent classics collection, 2012)
To keep Mrs. Erlynne's (Irene Rich) identity under wraps as the long-lost mother of upper-crust beauty Lady Windermere (May McAvoy), Lord Windermere (Bert Lytell) agrees to help finance her infiltration into top-hatted London aristocracy. But when tongues start clicking over her husband's involvement with the scandalous older woman, the young socialite gambles with her good family name by entertaining an affair of her own with courting cad Lord Darlington (Ronald Colman). Less adaptation than distillation, Ernst Lubitsch's version of Oscar Wilde's comedy of manners trades the playwright's perfumy verbiage for the visual importance of being Ernst ... Pushing the sang froid aesthetic of "The Marriage Circle", the movie is arguably the director's most austere silent, with the expressions, sets and décor pared down to an almost abstract level. The stripping-away of Wilde's epigrams and many of Lubitsch's own stylistics reminds of the harshness lying under so much of the director's insinuating surfaces ... [www.cinepassion.org]